2013
DOI: 10.1038/cgt.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Potent CD4+ T-cell epitope P30 enhances HER2/neu-engineered dendritic cell-induced immunity against Tg1-1 breast cancer in transgenic FVBneuN mice by enhanced CD4+ T-cell-stimulated CTL responses

Abstract: One of the major obstacles in human epidermal growth factor receptor (HER)-2/neu-specific trastuzumab immunotherapy of HER2/neu-positive breast cancer is the development of trastuzumab resistance, warranting the search for other therapeutic strategies. Although dendritic cell (DC) vaccines have been extensively applied in clinical trials for cancer treatment, the vaccination efficacy is still limited, mostly because DC vaccines are not sufficient to break tumor-associated antigen-specific self-immune tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…To date, although multiple approaches, such as selection of suitable DC subsets, adjuvants and different DC engineering methods, are being developed to improve the efficiency of DC-based vaccines, their clinical benefit is still limited [ [75] , [76] , [77] ].…”
Section: Vaccines Targeting Her2 In Breast Cancermentioning
confidence: 99%
“…To date, although multiple approaches, such as selection of suitable DC subsets, adjuvants and different DC engineering methods, are being developed to improve the efficiency of DC-based vaccines, their clinical benefit is still limited [ [75] , [76] , [77] ].…”
Section: Vaccines Targeting Her2 In Breast Cancermentioning
confidence: 99%
“…The result of in vivo depletion studies also established the role of both CD4 + and CD8 + T cells in inducing anti-tumor immunity (Chen et al 2001). Xie et al (2013) engineered DCs with two cancer antigens including the P30 peptide-derived from tetanus toxin (FNNFTVSFWLRVPKVSASHLE) and HER2derived peptides to generate highly efficient CD4 + and CD8 + T cell responses toward HER2-positive breast cancer. In another report, Viehl et al (2005) indicated that administration of DCs transfected with HER2 fused to Tat protein led to protection effects against tumor in FVB/N mice challenged with syngeneic HER2 overexpressing breast cancer cells.…”
Section: Dendritic Cell Vaccinesmentioning
confidence: 99%
“…In the second peptides set (Figure 1, peptides 15 and 16), w e i n t r o d u c e d t h e T h e l p e r e p i t o p e P 3 0 (FNNFTVSFWLRVPKVSASHLE), derived from tetanus toxoid, to improve the presentation of exogenous glycopeptides on the MHC complex and activate T cells for in vivo testing. 44 The tripartite vaccine 16 contains the Tn-modified MUC1 glycopeptide, the T helper epitope P30, and the high-affinity ligand 1 to enhance endocytosis by the C-type lectin MGL. Additionally, a corresponding control glycopeptide 15 lacking the MGL glycocluster ligand 1 was prepared.…”
Section: T H Imentioning
confidence: 99%